The thrombomodulin lectin-like domain does not change host responses to tuberculosis - Kager, Liesbeth M.; de Vos, Alex F.; Roelofs, Joris J. T. H.; van der Loos, Chris M.; de Boer, Onno J.; van’t Veer, Cornelis; Conway, Edward M.; Poll, Tom van der (Thrombosis and Haemostasis, 2014)
Tuberculosis (TB), caused by Mycobacterium (M.) tuberculosis, is a devastating infectious disease causing many deaths world-wide. Thrombomodulin (TM) is a multidomain glycoprotein expressed on all vascular endothelial cells. We here studied the role of the lectin-like domain of TM, responsible for a variety of anti-inflammatory properties of TM, during TB. We compared the extent of TM-expression in human lung tissue of TB and control patients. The, the role of the lectin-like domain of TM was investigated by comparing mice lacking this domain (TMLeD/LeD mice) with wild-type (WT) mice during experimental lung TB induced by infection with M. tuberculosis via the airways. Lungs were harvested for analyses at two, six and 29 weeks after infection. Lung TM-expression was downregulated in TB patients, which was not related to changes in the amount of endothelium in infected lungs. TMLeD/LeD mice showed unaltered mycobacterial loads in lungs, liver and spleen during experimental TB. Additionally, lung histopathology and cytokine concentrations were largely similar in TMLeD/LeD and WT mice, while total leukocyte counts were increased in lungs of TMLeD/LeD mice after 29 weeks of infection. Mortality did not occur in either group. The lectin-like domain of TM does not play an important role in the host response to M. tuberculosis infection in mice.
Keywords: Tuberculosis; inflammation; thrombomodulin; lung; infection